Understanding Student Self-Confidence: Impacts of Body Shaming, Self-Compassion, and Gender in Higher Education - Geni, Indra; Daharnis, Daharnis (Universitas Ahmad Dahlan, 2024)
Low self-confidence is a significant factor contributing to various academic and social difficulties among students, hindering their personal development. Previous research and observations at Padang State University indicate that many students continue to struggle with low self-confidence. This study aims to analyze the relationship between body shaming, self-compassion, and gender on student self-confidence, using a quantitative approach with a 2x2x2 factorial design. A sample of 362 students from the Faculty of Education, spread across six departments, was selected using cluster random sampling. Data analysis was conducted using three-way ANOVA. The results of the study revealed several key findings: (1) Overall, students at the Faculty of Education demonstrated high self-confidence, despite body shaming experiences; (2) In terms of self-compassion, students with higher levels of self-compassion exhibited greater self-confidence on average; (3) Gender did not significantly impact self-confidence, as there was little difference between male and female students; (4) Students who had not experienced body shaming had higher self-confidence than those who had been subjected to it; (5) There were significant differences in self-confidence based on self-compassion, with higher self-compassion correlating with higher self-confidence, while lower self-compassion was linked to lower self-confidence; and (6) There was no interaction effect between body shaming, self-compassion, and gender in explaining student self-confidence levels. This indicates that body shaming and self-compassion influence self-confidence similarly for both male and female students. These findings have implications for the development of counseling services in higher education, suggesting that targeted interventions can help improve student self-confidence, particularly by addressing body shaming and fostering self-compassion.